Do we need to change the way we compute the statute of limitations for labor claims? Implications of the Bureau of Electronic Parts of the Judiciary - Bulnes Alegría, Iván (2023)
The implementation of the Bureau of Electronic Parts of the Judiciary means a transformation in the practices of Peruvian litigants, since they have access to a technological tool that allows them to file pleadings and claims of all kinds before the courts of justice, using Internet connections continuously 24 hours a day, 365 days a year. This change has an impact on the criteria of accessibility to the courts used in labor proceedings to compute expiration periods and makes a change in the rule necessary, since the new technology allows permanent and uninterrupted access to the courts and renders anachronistic the criterion that counted expiration periods according to the possibility of the plaintiff to go in person to a physical court.